Aclimação e desempenho de tilápias (Oreochromis sp.) em sistema de recirculação de água do mar - Ostini, Sérgio [UNESP] (2002)
Red tilapia fingerlings were either directly transferred from freshwater to sea water (35‰) and also submitted to two different systems of gradual acclimation: daily increasing of 5‰ and the same gradual increment every two days. The study was set up at the Freshwater Prawn Laboratory, classes Aquaculture Center of the UNESP, Jaboticabal, SP. Three different size of red tilapia fingerlings were used: Trial 1 - 18.5 ± 1.2 mm, Trial 2 - 49.33 ± 4.45mm and Trial 3 - 71.9 ± 5.7 mm, respectively. Groups of 10 animals (n = 3) of each class were directly transferred to sea water in 10 L aquarium and maintained at 26oC, 35‰ salinity, and mortality were recorded every 15 minutes. For the gradual acclimation, 25 fish per parcel (n = 3) of each treatment were stocked in 100 L, conic-cylindrical tanks equipped with mechanical filter (40 L) made out of marine shell substrate. Fish were fed twice a day and water salinity and temperature and mortality were recorded every day. The experiment lasted for 20 days, 20% of the remained fish were weighed and data were analyzed through a 3 x 2 factorial. Results show that the tolerance of red tilapia to direct transfer to sea water increases with size until a certain extent, and that viability of a gradual acclimation to marine water as satisfactory for all tested class sizes but better survival rates were obtained with fingerlings measuring 49.3 mm total length, with a daily increase in salinity of 5‰. Better condition factor was presented by animals acclimated with 5‰ increase every two days